A Case of Pott's Disease with Epidural Abscess and Probable Cerebral Tuberculoma following Bacillus Calmette-Guérin Therapy for Superficial Bladder Cancer. Issue 1 (2010) - Josephson, Colin B; Al-Azri, Saleh; Smyth, Daniel J; Haase, David; Johnston, B Lynn
Abstract : Intravesical Bacillus Calmette-Guérin (BCG) immunotherapy is an accepted treatment for transitional cell carcinoma of the bladder. Carcinoma in situ of the bladder progresses to invasive muscular disease in approximately 54% of untreated patients, mandating early initiation of therapy once the diagnosis is confirmed. Should BCG treatment fail, an additional course of BCG combined with interferon-alpha, both administered intravesically, is a promising second-line immunotherapy. In greater than 95% of patients, BCG is tolerated without significant morbidity or mortality. However, both early (within three months of the original treatment) and late presentations of systemic infection resulting from intravesical BCG treatment have been described. The present study describes the course of a 75-year-old man with a late presentation of BCG vertebral osteomyelitis, discitis, epidural abscess, bilateral psoas abscesses and probable cerebral tuberculoma, following treatment regimens of intravesical BCG followed by intravesical BCG plus interferon-alpha 2b.